Nano-clays as Potential Pseudo-antibodies for COVID-19 - Sahel N. Abduljauwad; Taimur Habib; Habib-ur-Rehman Ahmed (Nanoscale Research Letters, 2020)
Abstract Despite several efforts, the development of an effective vaccine for COVID-19 may take a much longer time. Traditional/natural medicine, already experienced by humans, could be an earlier solution. Considering the research team’s experience in using nano-clays as high-affinity material for cancer metastasis, melanoma treatment, and bone regeneration, we propose to use these nano-clays for the prevention/treatment of COVID-19. Owing to high affinity, nano-clays would capture the viruses before the latter get engaged with human hACE2. In this study, molecular-level simulations and modeling of the interaction of coronavirus spike and hACE2 proteins were performed with and without nano-clays. The results showed a very high level of affinity/cohesiveness among SARS-CoV-2 spike and nano-clays as compared to the one between the former and hACE2. We premise that these nano-clays since already being used as drug carriers could also be injected as “clays-alone” medicine. Recommendations have also been provided for future in vitro and in vivo studies.